2010
DOI: 10.1124/jpet.110.168930
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β Signaling through Phosphatase and Tensin Homolog/Phosphoinositide 3-Kinase/Akt/Glycogen Synthase Kinase 3 Down-Regulates Blood-Brain Barrier Breast Cancer Resistance Protein

Abstract: Breast cancer resistance protein (BCRP) is an ATP-driven efflux pump at the blood-brain barrier that limits central nervous system pharmacotherapy. Our previous studies showed rapid loss of BCRP transport activity in rat brain capillaries exposed to low concentrations of 17-␤-estradiol (E2); this occurred without acute change in BCRP protein expression. Here, we describe a pathway through which sustained, extended exposure to E2 signals down-regulation of BCRP at the blood-brain barrier. Six-hour exposure of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 43 publications
(59 reference statements)
3
50
0
Order By: Relevance
“…GSK3␤ is active in resting cells through constitutive Tyr-216 phosphorylation, and PI3K/Akt-activating stimuli such as insulin can cause phosphorylation at Ser-9 and inactivation of GSK3␤ (8). The mechanism by which nongenomic activation of ER␤ might contribute to Ser-9 dephosphorylation and GSK3␤ activation in our study is still uncertain, but recent findings in rodent brain capillaries and breast cancer cells have shown that sustained ER␤ activation by extended exposure to estradiol resulted in PTEN activation and decreased GSK3 phosphorylation (19,27). Interestingly, part of the mechanism involved might also refer to the ER␤ response to Akt activation, as we demonstrated that activation of the PI3K/Akt pathway downregulated ER␤ degradation and activity in breast cancer cells (38).…”
Section: Discussionmentioning
confidence: 60%
“…GSK3␤ is active in resting cells through constitutive Tyr-216 phosphorylation, and PI3K/Akt-activating stimuli such as insulin can cause phosphorylation at Ser-9 and inactivation of GSK3␤ (8). The mechanism by which nongenomic activation of ER␤ might contribute to Ser-9 dephosphorylation and GSK3␤ activation in our study is still uncertain, but recent findings in rodent brain capillaries and breast cancer cells have shown that sustained ER␤ activation by extended exposure to estradiol resulted in PTEN activation and decreased GSK3 phosphorylation (19,27). Interestingly, part of the mechanism involved might also refer to the ER␤ response to Akt activation, as we demonstrated that activation of the PI3K/Akt pathway downregulated ER␤ degradation and activity in breast cancer cells (38).…”
Section: Discussionmentioning
confidence: 60%
“…To evaluate the effect of estradiol [34][35][36] on low-dose Epoxomicin treatment of NB cells we treated SH-SY5Y cells with betaestradiol for 24 h before exposing them to Epoxomicin for 24 and 48 h. Our results show that while estradiol treatment has a modest effect on cell cycle distribution of Epoxomicin treated cells for both 24 and 48 h (Fig. 4A).…”
Section: Effect Of Beta-estradiol Treatment On Proteasome Blockage Bymentioning
confidence: 81%
“…Rodent brain capillaries (from females and males) express both ERα and ERβ, with expression of the latter dominating at both the mRNA and proteins levels (Hartz, Madole, Miller, & Bauer, 2010;Hartz, Mahringer, Miller, & Bauer, 2010). Exposing rat and mouse brain capillaries to subnanomolar to nanomolar concentrations of estradiol (E2) rapidly (minutes) and reversibly reduces BCRP-mediated transport activity without altering protein expression (Fig.…”
Section: Bcrpmentioning
confidence: 99%
“…Exposing rat and mouse brain capillaries to subnanomolar to nanomolar concentrations of estradiol (E2) rapidly (minutes) and reversibly reduces BCRP-mediated transport activity without altering protein expression (Fig. 6) Hartz, Madole, et al, 2010). The reduction in activity is not altered by inhibitors of transcription and translation, but is blocked by Brefeldin A, an inhibitor of intracellular vesicle trafficking.…”
Section: Bcrpmentioning
confidence: 99%
See 1 more Smart Citation